IMPLEMENTASI GOOGLE MAPS DALAM SISTEM INFORMASI PENDATAAN LALU LINTAS BERBASIS WEB UNTUK DINAS PERHUBUNGAN KOTA BINJAI - Adek Maulidya, Adek Maulidya (STMIK KAPUTAMA, 2023)
Traffic refers to the movement of vehicles and people within the Road Traffic Space, while the Road Traffic Space itself pertains to the infrastructure designed for the transfer of vehicles, people, and/or goods, such as roads and supporting facilities. The traffic flow on toll roads is typically dense, especially during peak hours, resulting in traffic congestion. Conversely, when toll roads are less crowded, there is a tendency for drivers to accelerate their vehicles at high speeds, leading to numerous violations of traffic regulations on toll roads. The lack of discipline among drivers contributes to traffic accidents on toll roads, as evidenced by the increasing accident data. To ensure order and discipline in traffic and prevent even higher accident rates, several measures and efforts are presented through this study, including discipline and vehicle management on toll roads, enforcement and awareness of law enforcement officers, and efforts to improve legislation and regulations.